Plant regeneration of tea (Camellia sinensis) by in vitro culture of meristems, axillary buds and uninodal segments - Molina, Sandra P.; Pérez, María Laura; Rey, Hebe Y.; Mroginski, Luis A. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Plants of two clones (CH 14 INTA and CH 318 INTA) of tea (Camellia sinensis (L.) O. Kuntze) were regenerated by in vitro culture of three types of explants disinfected by immersion in 70% ethanol (1 min) and 1.5% sodium hypochlorite (20 min). The best medium for shoot regeneration from uninodal segments, for both clones, as well as for axillary buds of CH 14 INTA clone was ½ MS + 1 mg/L BAP. While the best medium for axillary buds of CH 318 clone was ½ MS + 1 mg/L BAP + 1 mg/L AG3. For meristems culture, the best medium, for both clones was ½ MS + 1 mg/L KIN + 1 mg/L AG3. Rooting of regenerated shoots were achieved by culture them on ¼ MS + 6 mg/L IBA.